Bahasa Malaysia: e-learning acceptance among year one pupils at Sekolah Kebangsaan Jengka 11, Bandar Tun Abdul Razak Jengka, Pahang Darul Makmur / Azmi Salim ... [et al.] - Salim, Azmi; Kamarudin, Zulkafle; Bahar, Marsyida; Mohd. Shah, Hamidah (2015)
Electronic learning (E-Learning) is a type of technology that can support education or learning where the medium used for teaching and learning (T & L) is using computer technology. A quantitative research method (descriptive) was adopted and designed to reflect the level of acceptance of E-Learning among the pupils of Year One Arif, Sekolah Kebangsaan Jengka 11, Bandar Tun Abdul Razak Jengka, Pahang. This study also aimed to investigate whether there were significant factors in students' intention to use E-Learning. Measurement model TAM (reduced) was used as a measurement tool in this study. Based on the model, a set of questionnaire was designed as an instrument to obtain information from respondents of this study. This instrument was divided into five (5) parts which were Demographic Information, the Use of Computers and the Internet, Measuring the Perception of E-Learning as Easy to Use, Measuring the Perception of E-Learning is Useful, Measuring the Attitude Towards Using E-Learning and Measuring the Behavior on Intention to Use. Social Science Statistical Package Software (SPSS) version 20 was used to analyze the data. The results showed that the level of acceptance of the pupils to the concept of E-Learning was high. For future studies, it is suggested that qualitative research methods be adopted by conducting interviews and observations. It is also recommended that subsequent studies take a larger sample size. In addition, different measurement tools should also be used to see the difference in the findings on the level of acceptance.